2023
DOI: 10.1021/acsami.3c10768
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering with Formamidinium Salts for Improving Ambient-Processed Inverted CsPbI3 Photovoltaic Performance: Intermediate- vs Post-Treatment

Tianxiang Li,
Wan Li,
Kun Wang
et al.

Abstract: Inverted all-inorganic perovskite solar cells (PSCs) have attracted increasing attention owing to excellent thermal stability, easy fabrication, and adaptable application as top cell in tandem solar cells. Apart from efficiency, ambient processing is desirable for practical production. To avoid water invasion in ambient air, surface engineering for perovskites is reported as a valid approach. However, most were performed by post-treatment, which hardly regulates the formation process of perovskite crystals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In addition to molecular passivation at the film surface, Fu et al reported that the 1,4-butanediamine (DAB) modification could polish the intrinsically formed lead-poor surface and eliminate the nonstoichiometric components [Figure 7C] [56] . Therefore, the deep-energy-level p-type traps are reduced, improving charge transfer at the CsPbI 3 /PCBM interface.…”
Section: Interface Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to molecular passivation at the film surface, Fu et al reported that the 1,4-butanediamine (DAB) modification could polish the intrinsically formed lead-poor surface and eliminate the nonstoichiometric components [Figure 7C] [56] . Therefore, the deep-energy-level p-type traps are reduced, improving charge transfer at the CsPbI 3 /PCBM interface.…”
Section: Interface Engineeringmentioning
confidence: 99%
“…(C) X-ray photoelectron spectroscopy results at the surface and 10 nm depth and schematic diagram of the electron-transport dynamics based on the reference and polished films. Copyright from Ref [56] .…”
Section: Interface Engineeringmentioning
confidence: 99%
“…Organic–inorganic hybrid perovskite solar cells (PSCs) have already obtained extensive attention on account of their excellent optoelectronic properties. So far, the power conversion efficiency (PCE) of organic–inorganic hybrid PSCs has rapidly surpassed 26% . However, their commercial applications are unfortunately restricted due to the volatilization and hydrophilicity of organic cations (MA + , FA + ). , Therefore, an all-inorganic CsPbX 3 (X = I, Br, Cl) perovskite has been synthesized by substituting the organic cations with inorganic Cs + . Among the CsPbX 3 group, CsPbBr 3 is well-known for the best stability, but the largest bandgap (∼2.3 eV) limits its photovoltaic performance. , In contrast, α-phase CsPbI 3 possesses the narrowest bandgap (∼1.7 eV), but it can spontaneously transform to the optically inactive δ-phase in the ambient environment, dramatically hindering its practical applications. , By regulation of the ratio of halogen atoms, the mixed-halide CsPbI 2 Br all-inorganic PSC with a PCE of 9.8% was established in 2016 for the first time . CsPbI 2 Br perovskite displays a narrower bandgap (∼1.9 eV) than CsPbBr 3 and a more excellent phase stability than CsPbI 3 even in the ambient atmosphere, making it possible for serving as an appropriate top cell in tandem solar cells .…”
Section: Introductionmentioning
confidence: 99%